Upaya Guru Bimbingan dan Konseling dalam Perencanaan Karier Siswa di MA - Nor Khofifatus (Conseils : Jurnal Bimbingan dan Konseling Islam, 2026)
His research is motivated by the efforts of guidance and counseling teachers in assisting students' career planning, from identifying talents and interests to determining college majors and job opportunities. This research focuses on: first, the role of guidance and counseling teachers in assisting students' career planning at MA Sumber Bungur Pakong; second, factors influencing students' career planning; and third, the media used by guidance and counseling teachers in assisting students' career planning. This research uses a qualitative approach with a phenomenological type. Data were obtained through observation, interviews, and documentation with two teachers as informants. Data validity was tested using source triangulation and technical triangulation. The results of the study indicate that: first, guidance and counseling teachers have an important role in assisting students' career planning through service programs such as classical guidance, consultation services, and campus expo activities. Second, factors influencing students' career planning include internal factors, such as students' abilities, talents, interests, motivations, and ambitions, as well as external factors such as support from family, teachers, friends, and the surrounding environment. Third, the media used are adjusted to the service theme, such as videos, leaflets, and career trees, with tools such as projectors, whiteboards, and markers. The most effective media used is video because it is considered to help students understand the services provided.